Manejo integrado de malezas en el cultivo de palma aceitera (Elaeis guineensis Jacq) - Cerezo Peñafiel, Alex David (2021)
Oil palm is a plant species of great economic importance worldwide for its oil, which is why it has become one of the main crops in the world. In Ecuador it represents one of the most representative crops as it is the second with the largest production area after rice cultivation. At the world level, Ecuador ranks sixth among the countries with the highest oil palm production. In cultivation there are phytosanitary problems that cause damage to trees reducing their productive capacity. Among the harmful organisms we find weeds, which are one of the main pests in the crop, they are harmful and compete strongly against the plant for nutrients, humidity, and sunlight, and eventually cause a decrease in yield. There is a great diversity of weed species that are present in the cultivation of oil palm, some become a potential problem, causing losses that exceed 20% in production. To control the pest, it is essential to implement integrated weed management systems to keep their populations at low levels that do not lead to lost economies. For the implementation of integrated weed management, control strategies should be selected that act harmoniously with each other, maintaining the least environmental impact.